2020
DOI: 10.3390/v12101122
|View full text |Cite
|
Sign up to set email alerts
|

Parenterally Administered Porcine Epidemic Diarrhea Virus-Like Particle-Based Vaccine Formulated with CCL25/28 Chemokines Induces Systemic and Mucosal Immune Protectivity in Pigs

Abstract: Generation of a safe, economical, and effective vaccine capable of inducing mucosal immunity is critical for the development of vaccines against enteric viral diseases. In the current study, virus-like particles (VLPs) containing the spike (S), membrane (M), and envelope (E) structural proteins of porcine epidemic diarrhea virus (PEDV) expressed by the novel polycistronic baculovirus expression vector were generated. The immunogenicity and protective efficacy of the PEDV VLPs formulated with or without mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Furthermore, we performed transcriptome analysis of jejunum tissues and identified the key PCGs, lncRNAs, and miRNAs involved in the immune responses of Min pigs infected with PEDV, which provided important information on virus-host interactions for deciphering the mechanism of virus infection. PEDV infection resulted in apoptosis and necrosis of small intestinal absorptive epithelial cells and a decrease in the ratio of villous height to crypt depth (26,27). In this study, all the infected piglets showed significant intestinal lesions, and the death individuals were more serious than the resistant individuals.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Furthermore, we performed transcriptome analysis of jejunum tissues and identified the key PCGs, lncRNAs, and miRNAs involved in the immune responses of Min pigs infected with PEDV, which provided important information on virus-host interactions for deciphering the mechanism of virus infection. PEDV infection resulted in apoptosis and necrosis of small intestinal absorptive epithelial cells and a decrease in the ratio of villous height to crypt depth (26,27). In this study, all the infected piglets showed significant intestinal lesions, and the death individuals were more serious than the resistant individuals.…”
Section: Discussionmentioning
confidence: 52%
“…CXCL9 secreted by PEDV-infected IPEC-J2 cells significantly regulated the number of T-cell subpopulations in the peripheral blood cells of piglets, and high expression of CXCL13 significantly increased the number of B-cell migrations ( 34 ). The synergistic role of CCL25 and CCL28 in translocating IgA cells into the intestine had been demonstrated in mice, and pigs immunized with CCL25/CCL28 adjuvant virus-like particles showed excellent immune protection against PEDV ( 26 , 35 ). In this study, CXCL8, CXCL2, CXCR6, CXCL9, CXCR4, CXCL8, CXCR6, CXCR4, CX3CL1, CCL19, CCL4, CCL21, CCL26, CCL28, and CCL11 showed higher expressions in the infected group than that in the control group, while CX3CR1, CXCL14, CCL5, and CCL16 had lower expressions in the infected group than that in the control group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These antibodies conferred protection against PEDV infection in Vero cells. Using a multicistronic baculovirus expression system, Hsu and colleagues successfully created VLPs incorporating the S, M, and E structural proteins of PEDV [ 123 ]. Their research revealed that pigs immunized intramuscularly developed a systemic immune response characterized by anti-PEDV S-specific IgG and cellular immunity.…”
Section: Current Status Of Ped Vaccinesmentioning
confidence: 99%
“…Antibodies targeting the receptor-binding domain (RBD) of the S1 protein can neutralize coronavirus infection by blocking virus binding to cell receptors . Considerable effort has been devoted to the development of PEDV vaccines that target the S1 protein. However, there is still a lack of effective vaccines against variant strains of PEDV, due to its low immunogenicity and the difficulty with rapidly replacing antigens. Ferritin (Fer) is essential for the proper storage of iron in the body.…”
mentioning
confidence: 99%